Vibrational spectra of bis(maltolato)oxovanadium(IV): A potent insulin mimetic agent - Parajón Costa, Beatriz Susana (2011)
The FTIR and FT-Raman spectra of the oxovanadium(IV) complex of 3-hydroxy-2-methyl-4-pyrone (maltol) bis(maltolato)oxovanadium(IV) were recorded and briefly discussed by comparison with the spectra of uncoordinated maltol and with some related species.